Dudchenko M. M. Micro and macrosemantics and logical compatibility of metaphorical images in translation - Dudchenko M. M. (Philological Treatises, 2020)
The article deals with the analyses of mistakes in reproducing metaphorical images of the English poetry in Ukrainian poetic translations. Among these mistakes are the change of stylistic nature of metaphors, lack of correspondence of images with micro and macrosemantics of the context of the work, logical incompatibility of the components of metaphorical image, complications of images which cause difficulties for their comprehension.